Identification and Biological Activities of Long‐Chain Peptaibols Produced by a Marine‐Derived Strain of Trichoderma longibrachiatum. Issue 5 (May 2016) - Mohamed‐Benkada, Mustapha; François Pouchus, Yves; Vérité, Philippe; Pagniez, Fabrice; Caroff, Nathalie; Ruiz, Nicolas
Abstract : Six long‐chain peptaibols, 1  – 6, were identified from agar cultures of a marine‐derived Trichoderma longibrachiatum Rifai strain (MMS151) isolated from blue mussels. The structure elucidation was carried out using electrospray ionization ion trap mass spectrometry (ESI‐IT‐MS) and GC/EI‐MS. The long‐chain peptaibols exhibited the general building scheme Ac‐Aib‐Ala‐Aib‐Ala‐Aib‐ XXX ‐Gln‐Aib‐Vxx‐Aib‐Gly‐ XXX ‐Aib‐Pro‐Vxx‐Aib‐ XXX ‐Gln‐Gln‐Pheol and were similar or identical to recurrent 20‐residue peptaibols produced by Trichoderma spp. Three new sequences were identified and were called longibrachins A‐0, A‐II‐a, and A‐IV‐b. The isolated peptaibols were assayed for cytotoxic, antibacterial, and antifungal activities, and acute toxicity on Dipteran larvae. Abstract :